Determinants of credit risk in lower-middle-income countries: Evidence from interest spread, efficiency, and macroeconomic factors - Budhathoki, Prem Bahadur; Karki, Murari; Lama, Padam Bahadur (The Economics and Finance Letters, 2025)
The study examines the influence of interest rate spread, efficiency, and macroeconomic factors on credit risk by analyzing a sample of lower-middle-income countries (LMICs) worldwide. It utilizes secondary data from 25 LMICs over the period 2000-2021 and employs the Pooled Ordinary Least Squares (POLS), Fixed-Effect (FE), and Random-Effect (RE) estimators. The baseline model indicates that the interest spread increases credit risk in LMICs. This finding is supported by sensitivity analysis. Additionally, the results reveal that inefficient banks produce higher non-performing loans (NPLs) in LMICs. Conversely, an increase in the capital ratio reduces NPLs, a result confirmed by sensitivity analysis. The presence of excess liquidity and minimal competition contribute to the rise of NPLs in LMICs, with further validation from the consistency check. Economic growth is associated with a reduction in credit risk faced by banks in LMICs. The relationship between inflation and credit risk remains inconclusive. Policymakers and regulators can utilize these findings to implement effective corrective measures before banks become insolvent due to high NPLs, thereby protecting banks from bankruptcy and safeguarding the real economy from shocks.